Radiation Exposure Reduction and Patient Outcome by Using Very Low Frame Rate Fluoroscopy Protocol (3.8 + 7.5 fps) During Percutaneous Coronary Intervention - Gupta, Ankush; Chhikara, Sanya; Vijayvergiya, Rajesh; Barwad, Parag; Prasad, Krishna; Datta, Rajat; Mahesh, Nalin K.; Maurya, Preetika; Singh, Navreet (Frontiers in Cardiovascular Medicine, 2021)
OBJECTIVES: In this study, we intend to analyze the feasibility and efficacy of very low frame rate fluoroscopy (VLFF) protocol using a combination of 3.8 fps and 7.5 fps while performing Percutaneous Coronary Intervention (PCI). METHODS: A retrospective cohort including 193 patients undergoing PCI under the VLFF protocol (Post-VLFF group) was compared with a retrospective cohort of 133 patients, who underwent PCI prior to implementation of VLFF protocol (Pre-VLFF group). In the Pre-VLFF group, all PCIs were performed using fluoroscopy frame rate of 15ps. In the Post-VLFF group, 3.8fps was used to guide catheter engagement, coronary lesion wiring, pre-and post-dilation, and 7.5fps was used for lesion assessment and stent placement. Increasing use of fluoroscopic storage in place of cineangiography was also encouraged. Cine acquisition in both groups was performed at 15fps. Primary endpoint was radiation exposure measured by Air Kerma. Secondary endpoints were procedure related outcomes and patient related outcomes (Major Adverse Cardiac Events including all-cause mortality, Target Lesion Failure, Myocardial Infarction, and Stroke). RESULTS: Post-VLFF group showed 74.7% reduction in Air Kerma as compared to Pre-VLFF group (433±27mGy vs 1714±140mGy; p<0.0001), with no increase in the fluoroscopy time (15.38±0.98minutes Post-VLFF vs 17.06±1.29minutes Pre-VLFF; p=0.529) and contrast volume (116.5±4.9ml Post-VLFF vs 116.7±6ml Pre-VLFF; p=0.700). Both groups had comparable procedural success and complications rates as well as incidence of MACE. CONCLUSIONS: The very low frame rate fluoroscopy protocol is a feasible, effective, and safe method to significantly reduce the radiation exposure during PCI without any compromise on procedural and patient outcomes.